Gen Z Muslimah Fashion Preferences Emphasizing Formality and Feminine Elegance: Preferensi Busana Muslimah Gen Z yang Menekankan Formalitas dan Keanggunan Feminin - Diah Krisnaningsih (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Muslimah fashion evolves by blending global trends with Islamic values, yet its alignment with Generation Z’s preferences remains underexplored. Gap: Limited research exists on how Gen Z’s aesthetic and religious values intersect in Muslimah fashion, particularly in academic settings. Aim: This study examines fashion trends and purchasing behavior among Muslimah students at Universitas Muhammadiyah Sidoarjo (UMSIDA) to support MSME product segmentation. Methods: Using a descriptive quantitative approach, data from 139 female students aged 19–24 were analyzed. Results: Findings reveal 74.8% prefer formal styles for academic/professional settings, dominated by Feminine-Casual and Feminine-Classic styles, characterized by pastel tones, modest embellishments, and breathable fabrics. Novelty: This study highlights how Gen Z integrates global trends, such as Korean aesthetics, with Islamic dress codes. Implications: Insights guide MSMEs in designing fashionable yet religiously compliant products for Gen Z Muslimah consumers. Highlights: Fashion Preference: UMSIDA Gen Z students favor formal attire with Feminine-Casual and Feminine-Classic styles. Cultural Integration: Korean-inspired trends blend with Islamic modesty, emphasizing pastel tones and simple designs. MSME Opportunity: Insights support tailored product segmentation for Muslimah fashion in academic and professional markets. Keywords: Muslimah Fashion, Gen Z, Consumer Behavior, Feminine Style, MSMEs